Post caesarean section wound infections at Rahima Moosa Mother and Child Hospital - Temenu, Adebowale Victor (My University, 2019)
Introduction Caesarean section is a surgical intervention commonly performed as part of obstetric care services globally. It is a life-saving procedure for either a pregnant woman or her baby or both. The World Health Organisation recommends that C/S should be perform when it is medically necessary. Caesarean section is associated with a myriad of maternal morbidities and mortality, including and not limited to postoperative wound infections. The Rahima Moosa Mother and Child Hospital alone had a high caesarean section rate of over 40% in 2017. Objectives To determine the in-hospital admission (readmission) rate for post caesarean section wound infections, to characterise the risk factors for post caesarean sections wound infections, and to describe the morbidities, microbiology pattern, preoperative and postoperative antibiotic usage in post caesarean section wound infections at Rahima Moosa Mother and Child Hospital. Methods This was a retrospective descriptive study. Medical records, labour ward records, caesarean section theatre records, admission ward records and outpatient ward records of all patients, age 18 and above, who had caesarean sections from 01 Jan 2017 to 30 June 2017, and present with post caesarean section wound infections were reviewed. Data extracted were uploaded unto the Redcap data online platform. The data were statistically analysed. Results Two thousand seven hundred and forty-six caesarean sections were performed in the first half of 2017, representing a caesarean section rate of 41.9%, a post caesarean section wound infection rate of 2.91%, and an in-hospital admission (re-admission) rate of 1.31%. The study population were largely healthy, as 83% had no known comorbidity. Black Africans disproportionately suffer more from post-Caesarean wound infection: prolonged labour, higher number of vaginal examinations, having an emergency caesarean section and the skill of surgeons may have played a role in the post caesarean section wound infections in this study. The morbidities associated with post caesarean section wound IV infections were not life threatening, as more than half the patients were managed as outpatients. Among the readmitted patients, 50% had superficial wound sepsis. The incidence of deep tissue/organ involvement were very low: acute severe maternal morbidity occurred in 7.2% of cases, comprising of one patient requiring a subtotal abdominal hysterectomy with repair of bladder injury and another patient requiring a total abdominal hysterectomy with left salpingo-oophorectomy who later required ICU admission and dialysis for acute kidney injury. In addition, here was one High Care Area admission for management of severe preeclampsia, while no mortality occurred. The microbes identified were skin and vaginal flora and the most common isolated organism was Staphylococcus aureus. Empirical broad-spectrum antibiotics: a triple regimen of ampicillin, gentamycin and metronidazole, and a co-amoxiclav based antibiotics regimen that cover Gram-positive, Gram-negative and anaerobes were found to be largely effective in the management of post caesarean section wound infections. Conclusion Although the caesarean section rate is high in this study setting, the in-hospital admission rate for post caesarean section wound infection is very low. Intrapartum events play a role in the post caesarean wound infections. The morbidities associated with post caesarean section were not life threating as more than half were managed as outpatients and the majority of the admitted patients had superficial wound sepsis. The study further indicates that Staphylococcus aureus is the most preponderant microbe isolated, and that empirical broad-spectrum antibiotics are effective in managing post caesarean section wound infection.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Obstetrics and Gynaecology.